Analisis Perbandingan Quality of Service VSAT IP dan VSAT Star Telkomsat - Pandu Laksana; Isnawati, Anggun Fitrian; Aditya Rizki Noermartyas (JURNAL NASIONAL TEKNIK ELEKTRO, 2024)
Technological developments and the increase in internet users, estimated to reach 185 million in early 2024, have driven the need for reliable communication network services, especially for underdeveloped, frontier, and outermost (3T) areas in Indonesia, where internet coverage is still minimal. Based on these problems, telecommunications service providers need to prepare appropriate designs to provide optimal service to customers by providing a quality network. Telkomsat offers solutions through satellite-based services, especially very small aperture terminals (VSAT). Quality of service (QoS) testing is carried out by measuring throughput, packet loss, delay, and jitter using transmission control protocol (TCP) and user datagram protocol (UDP) data to compare the performance of VSAT IP and VSAT Star. The results show that VSAT Star is superior in throughput and delay, with an average throughput of 8.79 Mbps and an average delay of 12.32 ms. This is better than VSAT IP which only produces 6.43 Mbps and 83.94 ms. Both services have the same average packet loss of 0%. However, VSAT IP is more stable in terms of jitter with an average value of 0.36 ms compared to VSAT Star which produces 1.05 ms. In the ping test to the public domain (Google.com), VSAT Star showed an excellent average value of 38.55 ms compared to 584.05 ms for VSAT IP. Overall, VSAT Star has greater potential because of its advantages such as auto point, larger bandwidth, and lower delay.